Exploring family business brands: Understanding predictors and effects. Issue 1 (March 2019) - Barroso Martínez, Ascensión; Sanguino Galván, Ramón; Botero, Isabel C.; González-López, Óscar R.; Buenadicha Mateos, María
Abstract: Family business brands are said to represent a source of differentiation that can create benefits for family firms in today's competitive market. However, research finds that not all family businesses are likely to promote their family business nature as part of their marketing efforts. Given the limited understanding that we have regarding which family firms promote their family business brand, and the effects that family business brand promotion can have on performance outcomes of the firm, this paper explores the extent to which family ownership and firm age affect the communication of the family business brand in corporate websites. Additionally, it analyzes the effects of communicating the family business brand on firm revenue, and how website quality moderates this relationship. We rely on data from the Global Family Business Index and the coding of the top 300 family firm websites to test our ideas. Results indicate that a higher percentage of family business ownership is related to the communication of the family business brand in the 300 largest family businesses. Additionally, the communication of the family business brand is also positively related to the revenue of the firm, particularly for family firms that have less complex websites. We discuss the implications of these results for future research and practice.